Tari Serampang Dua Belas: Sejarah dan Eksistensinya Hingga Kini - Fachri Syauqii (Medan Resource Center, 2021)
This article discusses the Serampang twelve dance which is a traditional dance of the Malay coastal community of East Sumatra. This research uses literature review method. The data used are taken from books, journals, seminar papers, theses and others that are supportive and representative. The findings of this research are that the history of the Serampang Twelve dance is rooted in the Malay Ronggeng tradition. In the ronggeng Malay section, the Sari Island dance is performed, which is still irregular. Then, this dance was composed by Guru Sauti with twelve patterns so that it was accepted by the community. For his services, this dance can be learned easily by all groups. In this dance, there is a story of a meeting between a young couple who finally decided to have a lifelong marriage. In fact, this dance still exists and is still being studied by young people today.